A COMPARISON OF DIFFERENCE COURT FLOORING ON RUNNING SPEED PERFORMANCE OF FUTSAL PLAYERS - Rongsombut, Kerkwit; Makaje, Niromlee; Ruangthai , Ratree; Tanphanich , Amnuay (Academic Journal of Thailand National Sports University, 2019)
The purpose of this research was to a compare of running speed performance on four type of fusal surfaces: wooden parquet surface, concrete hard flat surface, synthetic rubber surface and plastic tile surface. Twelve male futsal players aged 18 - 22 years of Kasetsart University, Kampangsean campus team participated in this study. Running speed performance tests investigated were straight sprint, shuttle run, zig zag run, multi-direction speed and reactive agility, with all tests for running measured in two sets without ball and with ball respectively. Data were analyzed by using mean, standard deviation and one–way ANOVA with repeated measure. Multiple comparisons were performed using the Tukey method. All test used the 0.05 level of significance. The result showed that all running speed performance test including straight sprint, shuttle run, zig zag run, multi-direction speed and reactive agility in four futsal surface were significantly different (P<0.05). Therefore, this study provided information about the effect of different futsal surfaces on speed running performance. It would be a useful task for the design of suitable training programs for each type of futsal playing surface.